Introduktion til Religionsvidenskabeligt Tidsskrift - Bilde, Per (Religionsvidenskabeligt tidsskrift, 1982)
This editorial announces the founding of a new scientific journal in Denmark entitled Religionsvidenskabeligt Tidsskrift (“Journal for the Scientific Study of Religion”). The goal of the Journal is to create a forum of research, information and debate within the field of the humanistic, scientific study of religion. “Religionsvidenskabeligt” does not in any way refer to a particular school or a special area of the study of religion. It refers, in fact, to the holistic study of religions based upon rigorous, scientific methods. The subjects under study will be religions, world views and parareligious phenomena. The methods represented by the various contributions will span such diverging approaches as philology, phenomenology, history, psychology, semiotics, sociology and systematic philosophy. Our main concern here is confrontation between the various disciplines based upon themes chosen by the staff for each issue. An equally important concern is that of informing our readers concerning results from the study of religion. The Journal will therefore offer book reviews, review articles, informative notes and debate series. The audience intended for the Journal are teachers, scholars and students of the study of religion as well as scholars from other fields of study, theologians, priests and others interested in religion.